Supplemental Sugar Is Required for Sex Pheromone Biosynthesis in Mythimna separata - Zhang, Yaling; Zhang, Yuanchen; Yao, Shuangyan; Wang, Gaoping; Wei, Jizhen; Du, Mengfang; An, Shiheng; Yin, Xinming (Frontiers in Physiology, 2020)
Supplemental nutrients of adult moths maximize moth fitness and contribute to the pollination of many plants. Previous reports have revealed that sugar feeding promotes to sex pheromone biosynthesis by increasing the haemolymph trehalose concentration in mating moths. Here, Mythimna separata adults were employed as a model to investigate the effect of sugar feeding on sex pheromone biosynthesis. Results showed that in virgin females, sugar feeding markedly increased the concentrations of trehalose, pyruvic acid, and acyl-CoA in pheromone glands (PGs), which in turn led to an increase in sex pheromone titer, female ability to attract males and successfully mating frequency in sugar-fed females. Consistently, sugar-fed females laid more eggs than water-fed females. Furthermore, the refeeding of starved females also caused significantly increase in the concentrations of trehalose, pyruvic acid, and acyl-CoA in PGs, thus facilitating a significant increase in sex pheromone production. Most importantly, RNAi-mediated knockdown of trehalase (leading to PG starvation) resulted in an increase in trehalose content, and decrease in the concentrations of pyruvic acid, and acyl-CoA in PGs, which in turn led to a decrease of sex pheromone titer, female ability to attract males and successful mating efficacy. Altogether, results revealed a mechanism by which sugar feeding contributed to trehalose utilization in PGs, promoted to significantly increased sex pheromone precursor by increasing the concentrations of pyruvic acid and acyl-CoA, and facilitated to sex pheromone biosynthesis and successful mating.